AI Based Gait Analysis for Digital Healthcare System - T.Divya Vani, R.Raja Kumar, K.Padmaja, Anjaneyulu Nelluru, T.R.Rajesh (International Journal of Advanced Science and Technology, 2020)
A tale ongoing acoustic input in view of figuring out how to lessen the length and to improve the advancement in the restoration is introduced. Wearable technology (WT) has risen as a reasonable way to give minimal effort computerized medicinal services and treatment course outside the clinical environment like emergency clinics and centers. Right now, show that the RTAF together with WTs can offer a fantastic solution to be utilized in recovery. The strategy for RTAF dependent on AI just as an investigation for demonstrating its effectiveness are introduced underneath. The outcomes show a quicker recuperation time utilizing RTAF. The proposed RTAF demonstrates an extraordinary potential to be utilized and conveyed to help advanced social insurance, treatment and restoration.